2016
DOI: 10.1590/s1806-37562015000000102
|View full text |Cite
|
Sign up to set email alerts
|

Association between physical activity in daily life and pulmonary function in adult smokers

Abstract: Objective: To determine whether the level of physical activity in daily life (PADL) is associated with pulmonary function in adult smokers. Methods: We selected 62 adult smokers from among the participants of an epidemiological study conducted in the city of Santos, Brazil. The subjects underwent forced spirometry for pulmonary function assessment. The level of PADL was assessed by the International Physical Activity Questionnaire and triaxial accelerometry, the device being used for seven days. The minimum le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…Bahmer reported that FEV 1 and peak expiratory flow were poor markers of physical activity in asthma patients, and they also found that reduced DL PA was associated with impulse oscillometric airway resistance and small airway dysfunction, which was not evaluated in our study. Interestingly, no consistent association has been found between active lifestyle/physical inactivity and pulmonary function (after adjustment for confounding factors) in healthy subjects, lung‐healthy adolescents, or adult smokers . In our study, the number of SPD was not associated with BMI, as previously reported for non‐obese individuals .…”
Section: Discussionsupporting
confidence: 53%
“…Bahmer reported that FEV 1 and peak expiratory flow were poor markers of physical activity in asthma patients, and they also found that reduced DL PA was associated with impulse oscillometric airway resistance and small airway dysfunction, which was not evaluated in our study. Interestingly, no consistent association has been found between active lifestyle/physical inactivity and pulmonary function (after adjustment for confounding factors) in healthy subjects, lung‐healthy adolescents, or adult smokers . In our study, the number of SPD was not associated with BMI, as previously reported for non‐obese individuals .…”
Section: Discussionsupporting
confidence: 53%
“…No causal relationships or long-term effects can be drawn from our cross-sectional analysis, but our results are in line with those from a longitudinal study observing that current smokers with moderate and high PA had a decreased decline in FEV 1 and FVC compared with smokers with low PA [ 36 ]; and as in our study, this association was not observed in never smokers. A study including only smokers did not find an association between the achievement of at least 150 min/week of MVPA and spirometric parameters [ 15 ]. However, observed differences may be related to diverse designs, population characteristics and definitions of being active [ 15 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In lung-healthy adolescents, no associations were found between accelerometer-based PA and a broad range of spirometric parameters [ 14 ]. In adults, results of a study among 62 smokers showed that lung function between inactive participants, defined as those who engaged in less than 150 min/week of moderate to vigorous PA (MVPA), and active ones did not differ [ 15 ]. Thus, the evidence is inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…In another study from Brazil, no correlation was found between pulmonary function and physical activity evaluated using an accelerometer in smoking adults. It was, however, emphasized that smoking history should be investigated thoroughly (13). In another study that observed the changes in smoking behaviors and related factors among smoking Australian young women for 10 years, the moderate and high physical activity levels were found to be positively correlated with being an ex-smoker.…”
Section: Discussionmentioning
confidence: 99%